ANALISIS PENGARUH KUALITAS PELAPORAN KEUANGAN DAN MATURITAS UTANG TERHADAP EFISIENSI INVESTASI - Annisa’ Dwi Rahmawati; Puji Harto (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to analyze the role of financial reporting quality and debt maturity in investment efficiency. The population in this study are manufacturing companies listed on the Stock Exchange during the period 2009 until 2011. Sampling in this study using purposive sampling method. The total numbers of samples are 189 companies. Data used in this study was company’s annual financial reports that were derived from sites Indonesia Stock Exchange. Then, data were analyzed using multiple linear regression analysis.The result of this study shows that financial reporting quality has positive and significant influence on investment efficiency. While debt maturity has no significant effect on investment efficiency. In addition, there no significant effect on the level of use of short term debt on financial reporting quality and investment efficiency.